Abreviasi Pada Media Berita Daring Bangkapos.Com: Tinjauan Morfologi - Sausan Afra; Noviatri Noviatri; Aslinda Aslinda (Universitas Andalas, 2023)
AbstractThis research is based on the productive use of morphological processes that change words into abbreviations, namely abbreviations in the online news media Bangkapos.com. This research aims to, 1) explain the forms of abbreviations used in the online news media Bangkapos.com and 2) explain the process of forming abbreviations used in the online news media Bangkapos.com.There are three research stages carried out in this research, namely 1) data provision stage, 2) data analysis stage, and 3) data analysis results presentation stage. At the data provision stage, the listening method was used with the basic tapping technique, then the Cakap Free Involvement Listening (SBLC) technique, and the note-taking technique as an advanced technique. At the data analysis stage, the method used is the matching method with the basic technique of Selecting Determining Elements (PUP) and the Contrasting and Comparing technique (HBB and HBS) as an advanced technique. The next stage, namely the stage of presenting the results of data analysis, uses formal and informal presentation methods. Based on the results of data analysis of abbreviations in the online news media Bangkapos.com, a) forms of use of abbreviations were found, namely: 1) abbreviations, 2) acronyms, 3) fragments, 4) contractions, 5) letter symbols, and 6) other forms of abbreviations. b) Based on the formation process, 1) abbreviations are formed through 10 processes, 1 of which is the process of forming a new finding; 2) the acronym was formed through 24 processes, 18 of which were new discoveries; 3) fragments are formed through 5 processes; 4) contraction is found through 3 processes; 5) letter symbols are formed through 5 marking processes; 6) other forms of abbreviation are formed through 5 processes in accordance with the Kridalaksana formulation, namely: affixation of abbreviations; reduplication over shortening; merging of abbreviations; disclaimer of abbreviations; abbreviation of abbreviations, and 1 other form was found, namely the form of abbreviation, a new finding from this research: the pun abbreviation form.